Studi Komparasi antara Model Pembelajaran PJBL dan CTL terhadap Hasil dan Keaktifan Belajar Siswa - Reni Ramdhani; Yosi Nur Kholisho; Baiq Desi Dwi Arianti (Universitas Hamzanwadi, 2018)
The aims of this study to determine: (1) differences in student learning outcomes between learning models PJBL and CTL, (2) differences in student learning activity between learning models PJBL and CTL. This research type is quantitative by using experiment method. The research design used is Quasi Experimental Design form Nonequivalent Control Groub Design. The population of this study is the entire class X TKJ SMK IP AL-MADANI with the number of 62 students. The sample of this research is class X TKJ 1 and class X TKJ 2. Technique of collecting data used is test and observation sheet. The test is used to measure students 'learning outcomes while the observation sheet is used to measure students' learning activeness. The analysis technique used is Pairet Sample T Test with the help of SPSS. The results of this study indicate that: (1) there are differences in student learning outcomes between learning models of PjBL and CTL (Ï 0.05); (2) there is a difference in student learning activity between PjBL and CTL learning models (Ï 0.05).